Características socioeconómicas de los ingresantes de pregrado a las Filiales de la Universidad Nacional de Trujillo, 2021 - García Alva, Deysy Mariella (2023)
The present work has been developed with the purpose of determining the socioeconomic characteristics of the undergraduate entrants to the Affiliates of the National University of Trujillo, during the year 2021. In relation to the type of research, it is mainly of a descriptive nature, which allowed organizing, summarizing and analyzing the information, in order to publicize the data obtained from the target population. The total population consists of 300 young men and women, who entered the year 2021, at the 16 Schools that are made up of the Branches of the National University of Trujillo: Huamachuco, Santiago of Chuco and Valle Jequetepeque. The sample size was 169 entrants, to whom the socioeconomic file, typical of the Social Service Unit, was applied, which served to determine the socioeconomic characteristics that they present at the beginning of their undergraduate training. Regarding the proposed hypothesis, it was considered that the socioeconomic characteristics that predominate in the undergraduate entrants to the Affiliates of the National University of Trujillo, during the year 2021 are: family disintegration, low economic income and limited access to basic services in housing; obtaining as results, that 67% of the entrants that make up the sample, present family disintegration, 56% have low economic income and 23% of them, did not have one or two basic services within their home. The research carried out favors the management of information that may be obtained from the entrants that belong to the Subsidiaries of the National University of Trujillo during the year 2021 and allows to visualize a specific reality about the socioeconomic characteristics that they present.